Reconsidering democracy promotion: a comparative analysis of Brazil and Turkey - Akgün, Merve Çalımlı (İstanbul Bilgi Üniversitesi, 2022)
ABSTRACT: Brazil and Turkey are two regional actors that have succinctly promoted democracy which marked an apparent shift in their foreign policies towards their regions between 2000 and 2015. This study intends to answer why Brazil and Turkey enacted democracy promotion in their foreign policies. Shedding light on the lack of comparative research on non-Western regional actors in comparative perspective across spatial and temporal dimensions, this study makes an empirical and theoretical contribution by looking at democracy promotion as a particular foreign policy outcome. Empirically, the study examines and maps all the democracy promotion practices by Brazil and Turkey, regardless of their limits, and chooses three cases amongst them as a within-case analysis for comparative research. For Brazil, Paraguay (2012), Peru (2000), Venezuela (2002, 2012), and for Turkey, Libya, Egypt, and Syria during the Arab Uprisings erupted in 2011 were subject to comparative analysis. Theoretically, positioning itself in alignment with Neoclassical Realism, the study aims to fill the gap between the increase in their relative power as a systemic variable and democracy promotion as an outcome of foreign policy. To this end, the study resorts to Role Theory and contends that the relative increase in their regional power was translated at the statelevel through pro-democratic regional leadership roles claimed by decision-makers, based on their states’ ideational and material capabilities. Building upon official reports, parliamentary speeches, newspaper articles, press releases, and interviews conducted in both countries; this study contends that securing/maximizing geostrategic commitments and retaining regional power motivated democracy promotion as a foreign policy outcome, which was caused by the relative increase in Brazil’s and Turkey’s regional power that resulted in decision-makers’ claim for the pro-democratic regional leadership role.

ÖZET: Brezilya ve Türkiye, 2000 ve 2015 yılları arasında bulundukları bölgelerde yer alan ülkelere uyguladıkları demokrasi teşviki politikalarla ön plana çıkmaktadır. Bu çalışma; Brezilya ve Türkiye’nin 2000 ve 2015 yılları arasında dış politikalarında neden demokrasi teşviki uyguladıkları sorusundan hareket eder. Batılı olmayan bölgesel aktörler üzerine mekânsal ve zamansal boyutlardaki karşılaştırmalı araştırmaların azlığına ışık tutan bu çalışma, dış politikada demokrasi teşvikini incelerken ampirik ve teorik bağlamda katkılar sunar. Ampirik olarak, verili zamanda Brezilya ve Türkiye’nin bölgelerinde uyguladıkları tüm demokrasi teşviki politikalarını araştırır ve vaka-içi analiz için Brezilya ve Türkiye’nin demokrasi teşviki politikası uyguladığı üç ülkeyi inceler. Bunlar; Brezilya vakası için, Paraguay (2012), Peru (2000) ve Venezüella (2002, 2012), Türkiye için; 2011 yılında ortaya çıkan Arap ayaklanmalarından hareketle; Libya, Mısır ve Suriye’dir. Teorik olarak, Neoklasik Realizm ile paralel bir çizgide ilerleyen çalışma, sistemsel bir değişken olarak ele alınan bölgesel güçteki göreli artış ile dış politika sonucu olarak demokrasi teşviki arasındaki boşluğu doldurmayı hedefler. Bu amaçla, bu çalışma Rol Teorisine başvurur. Buradan hareketle bu çalışma, bölgesel güçlerindeki göreli artışın, devletlerin fikirsel ve materyal kapasitelerine dayalı olarak karar vericiler tarafından talep edilen demokrasi yanlısı bölgesel liderlik rolü aracılığıyla devlet düzeyinde dönüştüğünü iddia etmektedir. Resmi raporlar, parlamento konuşmaları, gazete makaleleri, basın açıklamaları ve her iki ülkede yürütülen mülakatlardan oluşan bir kaynağın kullanıldığı bu çalışma, bölgesel güçlerindeki göreli artışın karar-alıcıları demokrasi yanlısı bölgesel liderlik rolü benimsemesine yol açması ile, jeostratejik bağımlılıklarını koruma/arttırma ve bölgesel güçlerini sürdürme motivasyonu güderek Brezilya ve Türkiye’nin demokrasi teşviki politikaları uyguladığını tartışmaktadır.
Demokrasi teşvikini yeniden düşünmek: Brezilya ve Türkiye karşılaştırmalı analizi
Keywords: Demokrasi Teşviki; Neoklasik Realizm; Rol Teorisi; Brezilya; Türkiye; Brazil; Turkey; Role Theory; Neoclassical Realism; Democracy Promotion